An Experimental Study on Particle and Physiochemical Properties of Turmeric Powder Ground at Different Temperatures (Global Journal of Science Frontier Research, 2020)
Turmeric was ground at different grinding temperatures viz. -80 o C, -40 o C, 0 o C and 40 o C. The powder obtained at different grinding temperatures were analyzed to classify the powder. For this reason, we determined the particle size distribution, flowability, surface morphology, mineral composition and physicochemical properties of the turmeric powders at different grinding temperature. Particle size shows inverse relation with grinding temperature and, flowability shows a direct correlation with the increase in grinding temperature. We analyzed the elemental content of the samples by using SEM EDX and, the result shows that turmeric powder imparts more bioavailability of minerals with a decrease in grinding temperature. There is good retention of physicochemical properties at lower grinding temperature (-80 o C) such as volatile oil (47.61%) and color (more brightness) as compared with those obtained at ambient temperature (40 o C). Color parameters also significantly varied with a decrease in grinding temperature.
Keywords: turmeric powder; grinding temperature; flowability; physicochemical properties; surface morphology; mineral composition